Correr, rezar e suar: a maratona como religião implícita - Flores, Patrícia Eugênio Valladão (2020)
This study aimed to analyze the marathon race in light of the concept of implicit religion. This concept encourages a search for "religion" where one would not expect to find it, including a variety of social phenomena, such as political engagement and sports. We have also employed C.G. Jung's notion of religion as a psychological function. The method used consisted of a combination of auto-ethnographic research based on the author's own experiences and qualitative interviews with professional and amateur marathon runners from Brazil and Kenya. Some parallels were identified between the concept of implicit religion and the marathon, but especially regarding Brazilian participants for whom this sport serves as a source of meaning in life and is connected to narratives of personal challenge. For Kenyans, however, the marathon is a professional activity that guarantees their survival, and religiousness appears as an explicit auxiliary element rather than an implicit phenomenon. The text concludes with a discussion of the limitations and contributions of the concept of implicit religion to the field of Study of Religion